ACCURACY OF ALLEN SCORE IN PREDICTING STROKE TYPE - Berna Detha Meilyana; Sri Andarini; Yati Sri Hayati, (The Malaysian Journal of Nursing (MJN), 2021)
Background: Stroke is an emergency condition that can cause a decrease in nerve function that is affected by injuries to the central nervous system. The initial examination is needed by nurses to find out the type of stroke that can determine the right treatment and quickly. Determination of the type of stroke is done by using a CT scan tool that has limited facilities in some hospitals, so we need a tool in the form of a stroke scoring that can be used. Aim: This study aims to determine the accuracy of Allen's score in predicting the type of stroke in patients Methods: This study uses an observational analytic method with a cross-sectional design. The sample selection uses purposive sampling with the number of respondents as many as 100 stroke patients. Observations were made using the Allen score. Results: The results showed 100 patients. Demographic characteristics of patients who have the most strokes are men, the age group that has the most strokes is 54-64 years, working privately. The sensitivity, specificity, NPP, NPN, and accuracy of Allen scores were 98.6%, 100%, 100%, 96%, and 99.0% in predicting the type of ischemic stroke. Whereas in predicting the type of hemorrhagic stroke, sensitivity, specificity, NPP, NPN, and accuracy are 83.3%, 92.6%, 71.4%, 96.2%, and 91%. Conclusion: Determining the type of stroke quickly and precisely, help is needed by using stroke scoring that can be done by nurses as a basis for providing collaborative care inpatient management.